Sociocultural perspectives on suicidal behaviour at the Coast Region of Kenya: an exploratory qualitative study. Issue 4 (6th April 2022) - Ongeri, Linnet; Nyawira, Miriam; Kariuki, Symon M; Theuri, Cyrus; Bitta, Mary; Penninx, Brenda; Newton, Charles RJC; Tijdink, Joeri
Abstract : Objectives: To explore perceived sociocultural factors that may influence suicidality from key informants residing in coastal Kenya. Design: We used an exploratory qualitative study design. Setting: Mombasa and Kilifi Counties of Coastal Kenya. Participants: 25 key informants including community leaders, professionals and community members directly and indirectly affected by suicidality. Methods: We conducted in-depth interviews with purposively selected key informants to collect data on sociocultural perspectives of suicide. Thematic analysis was used to identify key themes using both inductive and deductive processes. Results: Four key themes were identified from the inductive content analysis of 25 in-depth interviews as being important for understanding cultural perspectives related to suicidality: (1) the stigma of suicidal behaviour, with suicidal victims perceived as weak or crazy, and suicidal act as evil and illegal; (2) the attribution of supernatural causality to suicide, for example, due to sorcery or inherited curses; (3) the convoluted pathway to care, specifically, delayed access to biomedical care and preference for informal healers; and (4) gender and age differences influencing suicide motivation, method of suicide and care seeking behaviour for suicidality. Conclusions: This study provides an in depth understanding of cultural factors attributed to suicide in this rural community that may engender stigma, discrimination and poor access to mental healthcare in this community. We recommend multipronged and multilevel suicide prevention interventions targeted at changing stigmatising attitudes, beliefs and behaviours, and improving access to mental healthcare in the community.